Pelatihan Canva Untuk Membranding Media Sosial Sanggar Kesenian Budaya - Putri Ariska Rahmawati; Virginia Mandasari; Ayundha Evanthy; Dian Novia Listiarini (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
In the era of the industrial revolution 5.0, technologicalsophistication has really become the main tool in designing and designing a product that has a high market value. One example is the Internet. The internet itself has various models in it, adjusting each function so that it can help human activities quickly and easily. Especially in the Covid-19 condition, all activities that were originally offline turned into online. People are getting used to the use of digital applications. With the current condition, people are competing to market what is under their control to their target. Such as showing creativity in editing and designing digital works to make them look attractive in the eyes of the public. In addition, designing activities can be used as a means to brand a social media to create brand awareness to the public. There are many ways to create brand awareness. For example, by branding a social media account that can attract public attention. Therefore, the Student Service Program Team 86 UPN “Veteran” Jawa Timur conducted a Canva Training work program (digital application) to brand social media for the Surya Sumirat art studio located in Kelurahan Gayungan, Surabaya as well as introducing East Javanese arts and culture to the public, especially the younger generation. The results obtained after this training activity can apply the knowledge that has been obtained and can compare the social media accounts of art studio tours so that they can be better known.